The Role of Electronic Technology in Supporting Student Learning Activities in the Digital Era - Muhammad Aziz Al Afif; Zidni Ma'ruf; Muhammad Kofar; Nur Annisyah (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
This research looks into how digital tools help boost student learning at Sriwijaya State Polytechnic in today’s tech-driven world. This study employed a quantitative descriptive research design using a survey method, involving 56 students who were asked to complete a questionnaire using varying frequency scales. The data were analyzed using frequencies and percentages of the questionnaire. Digital electronic technology is really helpful for students. They find it easier to find the materials they need for learning. They can also connect with their teachers and friends during the learning process, this helps them do better in school. Students like using media because it is flexible and fun, it makes learning more interesting the good thing about technology is that it helps make school activities more exciting and effective. So digital electronic technology is very important for making learning. It should be used more in schools because it helps students learn in a way. Digital electronic technology is good, for education. It will keep helping students in the future.